Correlation between Radiologic Tumor Regression Grading (ycMRI) and Pathological Tumor Regression Grading (ypTRG) in Rectal Cancer - Velarasan, Kanmani; R, Deivanayagam; K, Nhishaa (Asian Pacific Journal of Cancer Care, 2025)
Aim: To study the correlation between clinical tumor regression grading by MRI (post RT) and the pathological tumor regression grading post neoadjuvant treatment in patients with rectal cancer. Materials and Methodology: Patients with histopathologically confirmed adenocarcinoma, locally advanced stages non metastatic were included. Exclusion criteria were patients with poor performance status, recurrence and patients with distant metastasis. Patient planned for radiation therapy with 3D conformal radiotherapy technique. Dose prescribed was 50.4Gy in 28 fractions along with Inj. 5FU and Leucovorin every 28 days. MRI was taken 6 weeks after radiation therapy. Tumor regression grading done using TRG score (MRI). Pathologic tumor response assessed by modified Ryan scheme for tumor regression. Correlation between MRI and pathological grading was done using Pearson correlation test. Results: Among 38 patients, 30 (89%) patients were males and 8 (11%) patients were females. Stage T3 (60.52%) was seen in 23 patients and T4 in 12 (31.57%) patients. Most common stage was IIIB in 23 (60.5%) patients followed by IIIC in 10 (26.3%) patients. 7 patients did not complete the entire course of radiation therapy and 6 patients defaulted for further clinical response assessment. Out of 25 patients, 19 (76%) patients underwent surgery. 6 patients were not willing for surgery due to fear of permanent colostomy. Among the 19 patients who underwent surgery, near complete response and partial response, were seen in 6 (31.6%) patients and 7 (36.9%) patients respectively and no response was seen in 6 (31.6%) patients. Clinical TRG (MRI) correlated well with pathological TRG (r = 0.97, p - 0.000). Conclusion: Clinical tumor regression grading by MRI correlated well with pathological tumor regression grading in our study. TRG has to be studied more in relevant to patient specific care.